A Follow-Up on Psychiatric Symptoms and Post-Traumatic Stress Disorders in Tuareg Refugees in Burkina Faso - Carta, Mauro Giovanni; Moro, Daniela; Wallet Oumar, Fadimata; Moro, Maria Francesca; Pintus, Mirra; Pintus, Elisa; Minerba, Luigi; Sancassiani, Federica; Pascolo-Fabrici, Elisabetta; Preti, Antonio; Bhugra, Dinesh Kumar (Frontiers in Psychiatry, 2018)
Introduction. The aim of this study was to carry out a two-year follow-up of refugees in a camp in Burkina Faso who had been interviewed previously. We also aimed to verify whether the general conditions in which they lived (e.g. protection by international organizations and the conclusion of negotiations and new hope of returning to Mali and reunification with surviving family members) would affect their mental health state. Methods. This is a cross-sectional study repeated over time on a cohort of refugees. People living in the Subgandé camp who had participated in the first survey in 2012 were identified using informational chains and approached for follow-up. Those who agreed were interviewed using the Short Screening Scale for PTSD and the K6 scale, French versions, to measure general psychopathology and the level of impairment. Results. The second survey shows a dramatic decrease in psychopathological symptoms (positivity at K6 scale). Improvement was also conspicuous in the frequency of people with stress symptoms (positivity at Short Screening Scale for PTSD and simultaneous positivity to K6 scale). The frequency of people screened positive at the Short Screening Scale for PTSD had also decreased, but the level of improvement was not pronounced. Conclusions. Our findings confirm that when physical conditions improve, psychological symptoms can also improve. Although in the studied sample psychological factors, such as the hope of returning to their own land and thus the possibility of maintaining ethnic cohesion, may have played a role, future research carried out with a proper methodology and sufficient resources to identify protective factors, is needed.